Prinsip Etik Keperawatan Respect to Others Berpengaruh Positif dengan Kinerja Perawat - Oktaviarini, Eva; Yetti, Krisna; Afriani, Tuti; Hariyati, Rr Tutik Sri; Wildani, Andi Amalia (Journal of Telenursing (JOTING), 2024)
This research aims to identify the relationship between the application of nursing ethical principles and nurse performance. The method used was quantitative with a cross-sectional approach to 129 nurses on duty in the Inpatient Room at RSAL Dr. Mintohardjo. Data analysis was carried out using a linear regression test. The research results show that factors related to performance include rank or class (p=0.037), respect for others (r=0.621), compassion (r=0.594), advocacy (r=0.610), intimacy (r=0.608). The regression test shows that 7 variables have a joint influence with the equation Y: 31.864+1.127*Respect to Others + 1.689*Education + 1.179 Length of Work - 1.919 *class rank + 0.755 Intimacy – 1.975*career level + 1.054 Advocacy. Respect to others partially has a positive effect on nurses' performance in nursing care (t=2.433, p=0.016), while the other variables are confounding variables (p>0.05, t<1.98). Variables namely education, rank/class, length of service, career level, advocacy, respect for others and intimacy influence nurse performance with a determined influence of 39.3%. Conclusions from the 4 sub-variables of ethical implementation where these four variables have a significant relationship independently to nurse performance. Keywords: Nurse Performance, Ethical Principles